The relationship between work stress and quiet quitting among generation Z employees - Veren, Karissa; Zamralita, Zamralita; Putra, Ismoro Reza Prima (Priviet Social Sciences Journal, 2026)
Quiet quitting represents a phase of disengagement in which employees continue to work but limit their efforts strictly to job descriptions. When this occurs on a massive scale, it hinders innovation, increases workload for engaged employees, and contributes to stagnant organizational growth. Previous studies have shown that quiet quitting is prevalent among Gen Z and is influenced by work stress. Work stress consists of challenge and hindrance stress, which affect individual performance differently. High levels of stress can also reduce productivity and lead to organizational losses. Therefore, further research is necessary to understand the relationship between these two types of work stress and quiet quitting. This study aims to examine the relationship between challenge stress, hindrance stress, and quiet quitting among Gen Z employees in Indonesia. A quantitative correlational design was used. The sample consisted of 212 Gen Z employees in Indonesia, selected through convenience sampling. Data were collected through an online survey using the Challenge and Hindrance-related Self-Reported Stress Scale by Cavanaugh et al. (1998) and the Quiet Quitting Scale by Galanis et al. (2023). The C-HSS contained 11 items, while the QQS comprised eight items, showing acceptable internal consistency (α>0.600). The results indicate that challenge stress is negatively correlated with quiet quitting, whereas hindrance stress is positively correlated. Challenge stress tends to enhance motivation and reduce quiet quitting tendencies, whereas hindrance stress increases withdrawal behaviors. These findings provide insights for organizations to develop strategies for managing Gen Z employees’ work-related stress and maintaining their engagement levels.